Avaliação da vida restante em fadiga de instrumentos rotatórios de NiTi ProTaper após uso clínico múltiplo - Evandro Pires Vieira (2007)
The purpose of this study was to evaluate the remaining fatigue life, as well as to compare surface damage due to structural fatigue, of rotary NiTi ProTaper instruments clinically used for cleaning and shaping the root canal system of five and eight molars. Forty-two sets of ProTaper instruments, type S1, S2, F1, and F2, were analyzed. They were divided into a Control Group (CG) with twelve sets of new instruments and three experimental groups: G1 and G2, each with ten sets of instruments, each set clinically used by an endodontist, with experience using the ProTaper system, in five and eight molars, respectively; and G3, with ten sets of instruments, each set clinically used in five molars by undergraduate students inexperienced with the system. Before and after the clinical use, all instruments were analyzed by optical microscopy for the presence of surface damage and three sets of each group of used instruments, randomly selected, were examined by scanning electron microscopy (SEM). The instruments were then tested in a bench device for evaluation of their fatigue resistance. The results obtained were statistically analyzed by one way ANOVA tests, at the 95% confidence level. A large amount of transverse microcracks were observed in all instruments, as well as a smaller number of longitudinal microcracks, indicating that they suffered structural fatigue. After the clinical use, a decrease in fatigue resistance was observed for all instruments evaluated. Operator experience affected the occurrence of plastic deformation and fracture of the files during shaping. The results obtained indicate that multiple clinical uses consume the fatigue life of the instruments, but the remaining fatigue life was essentially the same for instruments used in five and eight molars.